Binuclear Phthalocyanine‐Based Sandwich‐Type Rare Earth Complexes: Unprecedented Two π‐Bridged Biradical‐Metal Integrated SMMs. Issue 34 (10th July 2013) - Wang, Kang; Qi, Dongdong; Wang, Hailong; Cao, Wei; Li, Wenjun; Liu, Tao; Duan, Chunying; Jiang, Jianzhuang
<x xml:space="preserve">Abstract</x> Mini‐magnets: Sandwich‐type rare earth complexes involving two fused bis(phthalocyaninato) dysprosium(III) units (see figure), represent the first example of biradical–metal single molecule magnets (SMMs). These materials were synthesized and structurally characterized. Comparative investigation reveals the effective suppression of quantum tunneling of magnetization (QTM) by the π‐bridged biradical‐based antiferromagnetic interaction in the di‐dysprosium‐ion‐based SMM.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>